Stress of Habitat Fragmentation as a Cause for Multi-species Association: A Case from Little Andaman Island of India - Tagore, Johny Kumar; Raja, P.; Jansirani, P.; Soosairaj, S. (Indian Forester, 2024)
Habitat loss and fragmentation are conceivably the greatest threat to all life. Biodiversity around the world is significantly threatened by habitat loss. Destruction of habitat due to anthropogenic activities creates stress on native species, and hence, is forced to adapt to newer habitat else will have less chance of survival. Habitat fragmentation can decrease the range of such organisms resulting in pressure for survival and may lead to extinction. Organisms those co-inhibit have precise requirements and can be found only in restricted ecosystems. The nature of these associations may differ based on organisms’ evolution and environmental settings. Hence, ecological aspect of multispecies associations between every species are significantly hard to describe and measure the status of these interactions. Here, a case of how pressure on habitat destruction has resulted in synergy of some species difficult to coexist is discussed.